Respiratory Involvement in Patients with Neuromuscular Diseases: A Narrative Review. (26th December 2019) - Voulgaris, Athanasios; Antoniadou, Maria; Agrafiotis, Michalis; Steiropoulos, Paschalis
Abstract : Respiratory muscle weakness is a major cause of morbidity and mortality in patients with neuromuscular diseases (NMDs). Respiratory involvement in NMDs can manifest broadly, ranging from milder insufficiency that may affect only sleep initially to severe insufficiency that can be life threatening. Patients with neuromuscular diseases exhibit very often sleep-disordered breathing, which is frequently overlooked until symptoms become more severe leading to irreversible respiratory failure necessitating noninvasive ventilation (NIV) or even tracheostomy. Close monitoring of respiratory function and sleep evaluation is currently the standard of care. Early recognition of sleep disturbances and initiation of NIV can improve the quality of life and prolong survival. This review discusses the respiratory impairment during sleep in patients with NMDs, the diagnostic tools available for early recognition of sleep-disordered breathing and the therapeutic options available for overall respiratory management of patients with NMDs.